TINJAUAN YURIDIS PERATURAN STIMULUS EKONOMI SEBAGAI RESPON PANDEMI COVID 19 DALAM PEMULIHAN EKONOMI NASIONAL - Turnip, Anju Chornelus; Talubun, Richardus F. (LPPM Universitas Bina Insan, 2022)
Observing the current situation, the Covid-19 pandemic has an impact on the country's economic rotation. Business closures caused by decreasing income are one of the impacts of the Covid-19 pandemic. Closing jobs and decreasing income will of course have an impact on banking institutions. This is based on a credit mechanism that is problematic or bad because the debtor loses his job or decreases his income. Large-scale bad loans have a huge impact on banking institutions and can also help the national economy. Therefore, the government issued a regulation regarding economic stimulus as a response to the Covid-19 pandemic. The stimulus regulation provides rules in which, in this case, banks become a medium or tool for implementing a regulation. Basically, banks have an active role in running the national economy. However, in this case, of course, apart from these regulations giving a mandate to banking institutions, these regulations must also protect the interests of banks, where in this case banks also need income to carry out banking activities.